Synthesis, Characterization and Antimicrobial Activity of Cu(II), Co(II), Ni(II) and Zn(II) Complexes Derived from a New Mannich Base, N-(1-Morpholinobenzyl)benzamide and 1,2-Diaminobenzene - ROSELINE EMELDA, AMALI; JAYACHANDRAMANI, N.; RAVICHANDRAN, S. (Asian Journal of Chemistry, 2010)
This paper describes the synthesis of a new type of Mannich base, N-(1-morpholinobenzyl)benzamide (MBB), 1,2-diaminobenzene and its complexation behaviour with Cu(II), Co(II), Ni(II) and Zn(II) ions. The structural features of the complexes are characterized by microanalytical data, IR, UV-Vis, NMR and EPR technique. The electrolytic behaviour of the chelates was assessed from their molar conductance data. The monomeric nature of the chelates was confirmed from their magnetic susceptibility values. The X-band EPR spectra of the copper complex in DMSO at 300 and 77 K were recorded and their salient features are reported. The antimicrobial activity of the ligand and its complexes has been extensively studied on microorganisms such as Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa and the fungi Aspergillus niger and Rhizoctonia bataicola by well-diffusion technique using DMF as solvent. The values of zone of inhibition were found out at 37 ºC for a period of 24 h. It has been found that all the complexes have higher activity than the free ligand and the standard.